Application of platelet‐rich gel to enhance healing of transmetatarsal amputations in diabetic dysvascular patients - Serra, Raffaele (Int Wound J, 2013)
Transmetatarsal amputation (TMA) represents an effective surgical procedure used to treat several clinical conditions such as forefoot infection, gangrene and chronic ulceration in diabetic patients. TMA permits walking without the need for prosthesis, but nevertheless is burdened with a high complications rate. The aim of this study was to evaluate the possibility to use platelet gel (PG) as an adjuvant therapy when performing TMA procedure in diabetic patients. In a 6‐year period, 26 diabetic patients had undergone TMA procedure followed by autologous PG applications (group A) and 32 patients had undergone TMA as sole procedure (group B). After TMA procedure, the treatment is based on outpatient management and consists of a weekly platelet‐rich plasma gel application on the surgical wound for 1 month in group A and on clinical evaluation only for group B. For group A, healing rate was of 96·15% and one patient (3·84%) presented wound dehiscence, and no postoperative wound infections occurred. For group B, healing rate was of 59·37%; severe infection of the stump prompted to the proximal amputations in 40·62% of patients during the follow‐up period. PG application may be an effective adjuvant treatment to improve wound healing in diabetic dysvascular patients.